If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + 5 + -3 = 7(m + -1) Reorder the terms: 5 + -3 + 6m = 7(m + -1) Combine like terms: 5 + -3 = 2 2 + 6m = 7(m + -1) Reorder the terms: 2 + 6m = 7(-1 + m) 2 + 6m = (-1 * 7 + m * 7) 2 + 6m = (-7 + 7m) Solving 2 + 6m = -7 + 7m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7m' to each side of the equation. 2 + 6m + -7m = -7 + 7m + -7m Combine like terms: 6m + -7m = -1m 2 + -1m = -7 + 7m + -7m Combine like terms: 7m + -7m = 0 2 + -1m = -7 + 0 2 + -1m = -7 Add '-2' to each side of the equation. 2 + -2 + -1m = -7 + -2 Combine like terms: 2 + -2 = 0 0 + -1m = -7 + -2 -1m = -7 + -2 Combine like terms: -7 + -2 = -9 -1m = -9 Divide each side by '-1'. m = 9 Simplifying m = 9
| 12n-5=9n+3 | | 3(x-5)=-(x+3) | | 100=-(x-1) | | 28a+39-4a=319-11a | | =2x+7+3x | | 16-(6y-7)+3y=5(y+1) | | x^5+9x=0 | | 0=-t^2+6t | | T^4-8T^3-T+8= | | Y=90x | | =5x+6x | | 3/4+1/4=3/4-1/4 | | y=(ln(8x+5))(x^4) | | a+4a+32=12 | | 3+-4d=13 | | -7(11z+5)=5(-15z-7)-2z | | 3x^2+5x=8x | | 16+8y=8(y+2) | | 12a+2=6-7a | | 4(-6j+16)=3(-8j+3) | | log(4)(5x-13)=2 | | 3x^2+22+7=0 | | 3-4x=2-3x | | -40x-45+63x+27=-x+3x+9 | | -20p+4=4(-5p+1) | | =4(2+4k)+(7k+1)8 | | =(ln(8*x+5))(x^4) | | D=(ln(8*x+5))(x^4) | | 6=-3t^2+36t | | -6(-10-15w)=5(18w+12) | | 2x^2+y^2+2xy-2x=-1 | | 3t^2-11t+6= |